Mesoporous carbon coated nano ferroferric oxide and preparation method thereof

By using titanium dioxide by-product ferrous sulfate and coal coking by-product coal asphalt, combined with specific process steps, mesoporous carbon-coated nano-ferrous tetraoxide was prepared, which solved the low utilization rate and stable material of titanium dioxide by-product ferrous sulfate by-product titanium dioxide The problem of poor performance has achieved efficient and low-cost material preparation, which is suitable for a wide range of applications.

CN119284969APending Publication Date: 2025-01-10PANZHIHUA IRON & STEEL RES INST OF PANGANG GROUP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411540299.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The high-value utilization rate of ferrous sulfate by-product of titanium dioxide is low, which limits the sustainable development of the titanium dioxide industry in the sulfuric acid method, and the existing technology has failed to effectively use coal as a carbon source to prepare mesoporous carbon-coated nanotetroxide Tri-iron causes the material to have problems of agglomeration and poor stability.

Method used

Using titanium dioxide by-product ferrous sulfate and coal coking by-product coal asphalt as raw materials, grinding, calcining and washing through specific process steps to prepare mesoporous carbon-coated nano-ferrous tetraoxide, realizing the high-value utilization of the material. and structural stability improves.

Benefits of technology

The prepared mesoporous carbon coated nano iron tetroxide has a large specific surface area, good structural stability, small particle size and good dispersion. It is suitable for battery electrode materials, adsorption materials and catalysts, reducing production costs and equipment requirements. , with the prospect of large-scale production and promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of mesoporous carbon coated nano ferroferric oxide, which comprises the following steps: a) dissolving a titanium dioxide byproduct ferrous sulfate with water, filtering to remove insoluble substances, adding sodium sulfide into the filtrate, stirring, adjusting the pH value with ammonia water, reacting until no precipitate is generated, standing the solution, and filtering to remove the precipitate to obtain a refined ferrous sulfate solution; b) drying the refined ferrous sulfate solution to obtain a raw material of which the phase is FeSO4. 7H2O; then mixing a raw material of FeSO4. 7H2O with the coal pitch, and grinding to obtain mixture powder; and c) calcining the mixture powder under the protection of inert gas, cooling, and sequentially washing and drying to obtain the mesoporous carbon coated nano ferroferric oxide. Compared with the prior art, the titanium dioxide by-product and the coal coking by-product are adopted as the raw materials, specific process steps are matched, overall good interaction is achieved, and the prepared product is large in specific surface area, good in structural stability, small in particle size and good in dispersity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano materials, and more specifically to a mesoporous carbon-coated nano-ferrosoferric oxide and a preparation method thereof. Background Art

[0002] Carbon-coated nano-ferroferric oxide is widely used in microwave absorption materials, battery electrode materials, adsorption materials and catalysts due to its unique properties.

[0003] The main solid byproduct in the production process of titanium dioxide by sulfuric acid method is ferrous sulfate. The byproduct ferrous sulfate of titanium dioxide in my country reaches tens of millions of tons per year. At present, the high-value utilization rate of titanium dioxide byproduct ferrous sulfate is low, which limits the sustainable development of the titanium dioxide industry by sulfuric acid method. Every ton of titanium dioxide produced by sulfuric acid method will produce 3 to 4 tons of titanium dioxide byproduct ferrous sulfate. Only a small amount of these byproducts have been recycled and used for lithium battery positive electrode, water purifier and iron oxide pigment. Nano-ferroferric tetroxide is a widely used magnetic nanomaterial. The use of titanium dioxide byproduct ferrous sulfate to prepare nano-ferroferric tetroxide is an effective way to realize the resource utilization of titanium dioxide byproduct ferrous sulfate. At present, patent CN110683587A discloses a method for preparing nano-ferroferric tetroxide from titanium dioxide byproduct ferrous sulfate. Nano-sized ferroferric tetroxide gives the material a large specific surface area and many excellent physical and chemical properties; however, single-phase nano-ferroferric tetroxide has the defects of high density, easy agglomeration and poor stability. The development of composite materials with nano-ferroferric tetroxide as the core can greatly improve these defects and improve its application value. Carbon materials have high porosity and large specific surface area, stable thermal and chemical properties, and can effectively alleviate the agglomeration problem of nano-ferroferric oxide during application, improve the dispersibility of magnetic particles, and at the same time, the coating of the carbon shell can maintain the activity of the core as much as possible, extending the service life of the material. Coal tar, as a by-product of coal coking, is a carbon source with high carbon content, good fluidity, easy graphitization and low cost, and is very suitable for use as a precursor for preparing porous carbon materials. However, there is no related report in the prior art on the preparation of mesoporous carbon-coated nano-ferroferric oxide using coal tar as a carbon source. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a mesoporous carbon-coated nano-iron tetroxide and a preparation method thereof, using titanium dioxide by-products and coal coking by-products as raw materials, and the prepared mesoporous carbon-coated nano-iron tetroxide has a large specific surface area, good structural stability, small particle size and good dispersibility.

[0005] The present invention provides a method for preparing mesoporous carbon-coated nano-ferroferric oxide, comprising the following steps:

[0006] a) dissolving the titanium dioxide by-product ferrous sulfate in water, filtering to remove insoluble matter, adding sodium sulfide to the filtrate, stirring and adjusting the pH with ammonia water, reacting until no precipitate is generated, letting the solution stand, filtering to remove the precipitate, and obtaining a refined ferrous sulfate solution;

[0007] b) drying the refined ferrous sulfate solution obtained in step a) to obtain a raw material whose physical phase is FeSO4·7H2O; then mixing the raw material of FeSO4·7H2O and coal tar pitch, grinding them, and obtaining a mixture powder;

[0008] c) calcining the mixture powder obtained in step b) under the protection of an inert gas, washing and drying the mixture powder after cooling to obtain mesoporous carbon-coated nano-iron tetroxide.

[0009] Preferably, the amount of sodium sulfide added in step a) is 1% to 5% of the mass of the titanium dioxide by-product ferrous sulfate.

[0010] Preferably, the concentration of the ammonia water in step a) is 1 mol / L to 3 mol / L, and the pH is adjusted to 4 to 6.

[0011] Preferably, the standing time in step a) is 5 min to 15 min.

[0012] Preferably, the drying temperature in step b) is 70°C to 90°C.

[0013] Preferably, the mass ratio of the raw material of FeSO4·7H2O and coal tar pitch in step b) is (0.5-10):1.

[0014] Preferably, the inert gas in step c) is nitrogen or argon; the calcination process is specifically as follows:

[0015] The temperature is raised from ambient temperature to calcination temperature at a rate of 5°C / min to 15°C / min, the calcination temperature is 500°C to 600°C, and the calcination time is 0.5h to 3h.

[0016] Preferably, the washing process in step c) is performed 2 to 4 times with a mixed solvent of water and ethanol in a volume ratio of (1.5 to 2.5):1;

[0017] The drying process adopts a vacuum drying oven at 70° C. to 90° C. to dry to constant weight.

[0018] Preferably, the step c) further comprises:

[0019] The sulfur dioxide produced by calcination is absorbed by alkali solution; the alkali solution is sodium hydroxide solution or ammonia water.

[0020] The present invention also provides a mesoporous carbon-coated nano-ferroferric oxide, which is prepared by the preparation method described in the above technical solution.

[0021] The invention provides a preparation method of mesoporous carbon-coated nano-ferroferric oxide, which comprises the following steps: a) dissolving ferrous sulfate produced as a byproduct of titanium dioxide in water, filtering to remove insoluble matter, adding sodium sulfide to the filtrate, stirring, adjusting pH with ammonia water, reacting until no precipitate is generated, letting the solution stand, filtering to remove precipitate, and obtaining a refined ferrous sulfate solution; b) drying the refined ferrous sulfate solution obtained in step a) to obtain a raw material with a physical phase of FeSO4·7H2O; then mixing the raw material of FeSO4·7H2O with coal tar, grinding, and obtaining a mixture powder; c) calcining the mixture powder obtained in step b) under the protection of an inert gas, and washing and drying in sequence after cooling to obtain the mesoporous carbon-coated nano-ferroferric oxide. Compared with the prior art, the present invention adopts titanium dioxide by-products and coal coking by-products as raw materials, cooperates with specific process steps, achieves overall good interaction, and obtains a preparation method for mesoporous carbon-coated nano-iron tetroxide with simple preparation process, low equipment requirements, low process energy consumption, and low production cost, thereby realizing high-value utilization of titanium dioxide by-products and coal coking by-products by sulfuric acid method; and the prepared mesoporous carbon-coated nano-iron tetroxide has a large specific surface area, good structural stability, small particle size, and good dispersibility, and is suitable for application in battery electrode materials, adsorption materials, and catalysts, and has great prospects for large-scale production and promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the mesoporous carbon-coated nano-iron tetroxide prepared in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of mesoporous carbon-coated nano-iron tetroxide prepared in Example 2 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of mesoporous carbon-coated nano-iron tetroxide prepared in Example 3 of the present invention;

[0025] Figure 4 This is a scanning electron microscope image of the mesoporous carbon-coated nano-ferroferric oxide prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for preparing mesoporous carbon-coated nano-ferroferric oxide, comprising the following steps:

[0028] a) dissolving the titanium dioxide by-product ferrous sulfate in water, filtering to remove insoluble matter, adding sodium sulfide to the filtrate, stirring and adjusting the pH with ammonia water, reacting until no precipitate is generated, letting the solution stand, filtering to remove the precipitate, and obtaining a refined ferrous sulfate solution;

[0029] b) drying the refined ferrous sulfate solution obtained in step a) to obtain a raw material whose physical phase is FeSO4·7H2O; then mixing the raw material of FeSO4·7H2O and coal tar pitch, grinding them, and obtaining a mixture powder;

[0030] c) calcining the mixture powder obtained in step b) under the protection of an inert gas, washing and drying the mixture powder after cooling to obtain mesoporous carbon-coated nano-iron tetroxide.

[0031] The method firstly dissolves ferrous sulfate produced as a byproduct of titanium dioxide in water, removes insoluble matter by filtering, then adds sodium sulfide to the filtrate, adjusts the pH value with ammonia water after stirring, reacts until no precipitation is generated, and then allows the solution to stand, removes the precipitation by filtering, and obtains a refined ferrous sulfate solution.

[0032] In the present invention, the titanium dioxide by-product ferrous sulfate is a low-cost iron-containing compound, the main component of which is ferrous sulfate, and it also contains a small amount of free sulfuric acid and other metal ions. The present invention has no special restrictions on its source, and the source of the by-product of the sulfuric acid process well known to those skilled in the art can be used.

[0033] In the present invention, the water is preferably deionized water well known to those skilled in the art, which will not be described in detail in the present invention.

[0034] In the present invention, the amount of water used is preferably an amount that can completely and sufficiently dissolve the by-produced ferrous sulfate from titanium dioxide. In a preferred embodiment of the present invention, 5 L of water is used to dissolve 500 g of the by-produced ferrous sulfate from titanium dioxide.

[0035] In the present invention, the amount of sodium sulfide added is preferably 1% to 5% of the mass of the titanium dioxide by-product ferrous sulfate, and more preferably 2.5% to 3%. The present invention has no particular limitation on the source of the sodium sulfide, and commercially available products known to those skilled in the art can be used.

[0036] After sufficient stirring, ammonia water is added dropwise to adjust the pH; the concentration of the ammonia water is preferably 1 mol / L to 3 mol / L, more preferably 2 mol / L, and the adjusted pH is preferably 4 to 6, more preferably 5.

[0037] In the present invention, the standing time is preferably 5 min to 15 min, more preferably 10 min.

[0038] The refined ferrous sulfate solution is obtained. The method of the present invention dries the obtained refined ferrous sulfate solution to obtain a raw material whose physical phase is FeSO4·7H2O; then the raw material of FeSO4·7H2O is mixed with coal tar pitch, and ground to obtain a mixture powder.

[0039] In the present invention, the drying temperature is preferably 70°C to 90°C, more preferably 80°C.

[0040] In the present invention, the coal tar pitch, i.e., a byproduct of coal coking, is a carbon source with high carbon content, good fluidity, easy graphitization and low cost; the present invention has no special restrictions on its source, and the source of the byproducts well known to those skilled in the art can be used. The present invention uses titanium dioxide byproducts and coal coking byproducts as raw materials, and uses them as iron sources and carbon sources respectively to produce high value-added mesoporous carbon-coated nano-ferroferric oxide, thereby realizing the high-value utilization of titanium dioxide byproducts and coal coking byproducts, and has good economic benefits and environmental friendliness.

[0041] In the present invention, the mass ratio of the raw material of FeSO4·7H2O to coal tar pitch is preferably (0.5-10):1, more preferably (1-3):1.

[0042] In the present invention, the grinding method is preferably grinding in a ball mill for 20 min to 40 min to obtain a uniform mixture powder.

[0043] After obtaining the mixture powder, the present invention calcines the obtained mixture powder under the protection of an inert gas, and washes and dries the mixture powder in sequence after cooling to obtain mesoporous carbon-coated nano-ferrosoferric oxide.

[0044] In the present invention, the inert gas is preferably nitrogen or argon, more preferably nitrogen.

[0045] In the present invention, the calcination process is preferably carried out in a tube furnace well known to those skilled in the art; the calcination process is preferably specifically as follows:

[0046] The temperature is raised from ambient temperature to calcination temperature at a rate of 5°C / min to 15°C / min, the calcination temperature is 500°C to 600°C, and the calcination time is 0.5h to 3h;

[0047] More preferably:

[0048] The temperature is raised from ambient temperature to calcination temperature at a rate of 10°C / min, the calcination temperature is 500°C~600°C, and the calcination time is 1h~2h.

[0049] In the present invention, the cooling to ambient temperature is not particularly limited in the present invention.

[0050] In the present invention, the washing process preferably adopts a mixed solvent with a volume ratio of water to ethanol of (1.5~2.5):1 for washing 2~4 times, and more preferably adopts a mixed solvent with a volume ratio of water to ethanol of 2:1 for washing 3 times; the drying process preferably adopts a vacuum drying oven at 70°C~90°C to constant weight, more preferably 80°C.

[0051] In the present invention, the step c) preferably further comprises:

[0052] The sulfur dioxide produced by calcination is absorbed by an alkali solution; the alkali solution is preferably a sodium hydroxide solution or ammonia water.

[0053] The present invention adopts titanium dioxide by-products and coal coking by-products as raw materials, cooperates with specific process steps, realizes overall good interaction, and obtains a preparation method of mesoporous carbon-coated nano-iron tetroxide with simple preparation process, low equipment requirements, low process energy consumption, and low production cost, thereby realizing high-value utilization of titanium dioxide by-products and coal coking by-products produced by sulfuric acid process.

[0054] The present invention also provides a mesoporous carbon-coated nano-iron tetroxide, which is prepared by the preparation method described in the above technical scheme; the preparation method provided by the present invention utilizes ferrous sulfate, a by-product of titanium dioxide, and coal tar, a by-product of coal coking, as raw materials, and adopts a one-step solid-phase method to prepare the mesoporous carbon-coated nano-iron tetroxide. The prepared mesoporous carbon-coated nano-iron tetroxide has a large specific surface area, good structural stability, small particle size, and good dispersibility, and is suitable for application in battery electrode materials, adsorption materials, and catalysts, and has great prospects for large-scale production and promotion and application.

[0055] The invention provides a preparation method of mesoporous carbon-coated nano-ferroferric oxide, which comprises the following steps: a) dissolving ferrous sulfate produced as a byproduct of titanium dioxide in water, filtering to remove insoluble matter, adding sodium sulfide to the filtrate, stirring, adjusting pH with ammonia water, reacting until no precipitate is generated, letting the solution stand, filtering to remove precipitate, and obtaining a refined ferrous sulfate solution; b) drying the refined ferrous sulfate solution obtained in step a) to obtain a raw material with a physical phase of FeSO4·7H2O; then mixing the raw material of FeSO4·7H2O with coal tar, grinding, and obtaining a mixture powder; c) calcining the mixture powder obtained in step b) under the protection of an inert gas, and washing and drying in sequence after cooling to obtain the mesoporous carbon-coated nano-ferroferric oxide. Compared with the prior art, the present invention adopts titanium dioxide by-products and coal coking by-products as raw materials, cooperates with specific process steps, achieves overall good interaction, and obtains a preparation method for mesoporous carbon-coated nano-iron tetroxide with simple preparation process, low equipment requirements, low process energy consumption, and low production cost, thereby realizing high-value utilization of titanium dioxide by-products and coal coking by-products by sulfuric acid method; and the prepared mesoporous carbon-coated nano-iron tetroxide has a large specific surface area, good structural stability, small particle size, and good dispersibility, and is suitable for application in battery electrode materials, adsorption materials, and catalysts, and has great prospects for large-scale production and promotion and application.

[0056] To further illustrate the present invention, the following examples are described in detail. The raw materials used in the following examples of the present invention are a large amount of titanium dioxide byproducts and coal coking byproducts produced by Panzhihua Iron and Steel every year, wherein the main component of the titanium dioxide byproduct is ferrous sulfate, also known as titanium dioxide byproduct ferrous sulfate, and contains a small amount of free sulfuric acid and other metal ions. Because the titanium dioxide byproduct ferrous sulfate needs to be refined before use, as long as the ferrous sulfate produced by the sulfuric acid method titanium dioxide byproduct can be used as the basic raw material; the coal coking byproduct is coal tar, and the coal tar composition produced by different types of coal varies, but as long as the content of carbon in the composition is high, it can be used as a carbon source, and all coal tar carbon contents are very high, so the coal tar here is suitable for various types of coal tar; in the following examples, the microscopic morphology of mesoporous carbon-coated nano-ferroferric oxide is obtained by scanning electron microscopy, and the specific surface area is obtained by BET testing method.

[0057] Example 1

[0058] Dissolve 500g of titanium dioxide by-product ferrous sulfate in 5L of deionized water, filter out insoluble matter, add 12.5g of sodium sulfide to the filtrate, stir thoroughly, drop 2mol / L ammonia water to adjust the pH to 5.0, let the solution stand for 10 minutes until no more precipitate is generated, then filter out the precipitate to obtain a refined ferrous sulfate solution.

[0059] The refined ferrous sulfate solution was dried at 80°C to obtain a raw material whose main phase was FeSO4·7H2O, and then 30g of FeSO4·7H2O and 30g of coal tar were weighed, mixed and ground into uniform powder; the mixed powder was placed in a tube furnace, nitrogen was introduced, and the temperature was increased to 500°C at a heating rate of 10°C / min, and calcined for 1h. The calcined product was cooled to ambient temperature under nitrogen protection, washed three times with a mixed solvent of deionized water and ethanol in a volume ratio of 2:1, and then dried in a vacuum drying oven at 80°C to constant weight to obtain mesoporous carbon-coated nano-ferrosoferric oxide; sulfur dioxide produced by calcination was absorbed by sodium hydroxide solution.

[0060] The particle size of the prepared mesoporous carbon-coated nano-iron tetroxide is 30-100nm, and the particle size is uneven. The scanning electron microscope image is shown in Figure 1 , the specific surface area reaches 102m 2 ·g -1 .

[0061] Example 2

[0062] Mesoporous carbon-coated nano-ferroferric oxide was prepared according to the preparation process of Example 1, except that the mass ratio of FeSO4·7H2O to coal tar pitch was 2:1, and 40 g FeSO4·7H2O and 20 g coal tar pitch were weighed and mixed.

[0063] The particle size of the prepared mesoporous carbon-coated nano-iron tetroxide is 20-60nm, and the particle size is relatively uniform. The scanning electron microscope image is shown in Figure 2 , the specific surface area reaches 155m 2 ·g -1 .

[0064] Example 3

[0065] Mesoporous carbon-coated nano-iron tetroxide was prepared according to the preparation process of Example 2, except that the calcination temperature was 600°C.

[0066] The particle size of the prepared mesoporous carbon-coated nano-iron tetroxide is 25-80nm, and the particle size is relatively uniform. The scanning electron microscope image is shown in Figure 3 , with a specific surface area of ​​147m 2 ·g -1 .

[0067] Example 4

[0068] Mesoporous carbon-coated nano-iron tetroxide was prepared according to the preparation process of Example 2, except that the calcination time was 2 h.

[0069] The particle size of the prepared mesoporous carbon-coated nano-iron tetroxide is 20-50nm, and the particle size is relatively uniform. The scanning electron microscope image is shown in Figure 4 , with a specific surface area of ​​172m 2 ·g -1 .

[0070] In summary, the preparation method provided by the present invention is a one-step solid-phase reaction, the preparation process is simple, the energy consumption is low, the raw materials used are chemical by-products, the cost is low, and it is suitable for large-scale production; and the prepared mesoporous carbon-coated nano-iron tetroxide is a core-shell structure, which has the characteristics of large specific surface area, good structural stability, small particle size and good dispersibility.

[0071] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing mesoporous carbon-coated nano-ferroferric oxide, characterized in that: The following steps are involved: a) dissolving the titanium dioxide by-product ferrous sulfate in water, filtering to remove insoluble matter, adding sodium sulfide to the filtrate, stirring and adjusting the pH with ammonia water, reacting until no precipitate is generated, letting the solution stand, filtering to remove the precipitate, and obtaining a refined ferrous sulfate solution; b) drying the refined ferrous sulfate solution obtained in step a) to obtain a raw material whose physical phase is FeSO4·7H2O; then mixing the raw material of FeSO4·7H2O and coal tar pitch, grinding them, and obtaining a mixture powder; c) calcining the mixture powder obtained in step b) under the protection of an inert gas, washing and drying the mixture powder after cooling to obtain mesoporous carbon-coated nano-iron tetroxide.

2. The preparation method according to claim 1, characterized in that: The amount of sodium sulfide added in step a) is 1% to 5% of the mass of the titanium dioxide by-product ferrous sulfate.

3. The preparation method according to claim 1, characterized in that: The concentration of the ammonia water in step a) is 1 mol / L to 3 mol / L, and the pH is adjusted to 4 to 6.

4. The preparation method according to claim 1, characterized in that: The standing time in step a) is 5 min to 15 min.

5. The preparation method according to claim 1, characterized in that: The drying temperature in step b) is 70°C to 90°C.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the raw material of FeSO4·7H2O and coal tar pitch in step b) is (0.5~10):

1.

7. The preparation method according to claim 1, characterized in that: In step c), the inert gas is nitrogen or argon; the calcination process is specifically as follows: The temperature is raised from ambient temperature to calcination temperature at a rate of 5°C / min to 15°C / min, the calcination temperature is 500°C to 600°C, and the calcination time is 0.5h to 3h.

8. The preparation method according to claim 1, characterized in that: The washing process in step c) is performed by washing 2 to 4 times with a mixed solvent of water and ethanol in a volume ratio of (1.5 to 2.5):1; The drying process adopts a vacuum drying oven at 70° C. to 90° C. to dry to constant weight.

9. The preparation method according to any one of claims 1 to 8, characterized in that The step c) further comprises: The sulfur dioxide produced by calcination is absorbed by alkali solution; the alkali solution is sodium hydroxide solution or ammonia water.

10. A mesoporous carbon-coated nano-iron tetroxide, characterized in that: The method is prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing mesoporous nano ferroferric oxide particles from titanium dioxide byproduct ferrous sulfate

    CN110683587A